Application of the Snowball Throwing Method to Improve Arabic Speaking Skills in Grade VII Students at MTS Al-Hijrah Integrated Lubuk Dendang Deli Serdang - Ade Dwi Juliani Ritonga; Salamuddin Salamuddin (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to determine the effectiveness of the Snowball Throwing method in improving Arabic speaking skills (maharah al-kalam) in grade VII students. Speaking skills are one of the important aspects of learning Arabic, but they are often hampered by low active student participation and the dominance of conventional learning methods. For this reason, this study uses a qualitative approach with a descriptive type, in order to describe in depth the process of applying the Snowball Throwing method in the context of real learning. Data collection techniques include observation, interviews, and documentation of grade 7C students at SMPS IT Al Hijrah. The results of the study show that the Snowball Throwing method is able to create an interactive and fun learning atmosphere, increase students' confidence, and encourage them to be more active in using Arabic orally. Thus, this method has proven to be effective as an alternative strategy in learning maharah al-kalam at the junior high school level.